2006
DOI: 10.1021/ja056031h
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Adsorption Studies of a 14-Amino Acid Leucine-Lysine Peptide onto Hydrophobic Polystyrene and Hydrophilic Silica Surfaces Using Quartz Crystal Microbalance, Atomic Force Microscopy, and Sum Frequency Generation Vibrational Spectroscopy

Abstract: The adsorption of a 14-amino acid amphiphilic peptide, LK14, which is composed of leucine (L, nonpolar) and lysine (K, charged), on hydrophobic polystyrene (PS) and hydrophilic silica (SiO2) was investigated in situ by quartz crystal microbalance (QCM), atomic force microscopy (AFM), and sum frequency generation (SFG) vibrational spectroscopy. The LK14 peptide, adsorbed from a pH 7.4 phosphate-buffered saline (PBS) solution, displayed very different coverage, surface roughness and friction, topography, and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
253
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(277 citation statements)
references
References 63 publications
19
253
1
4
Order By: Relevance
“…The latter constraint, the distance of the α-carbon to the surface, can be estimated from the peptide sequence and the known orientation of the entire peptide on hydrophobic surfaces. It has been shown that the peptide assumes an α-helical secondary structure on polystyrene and that the leucine ensemble is generally oriented towards the interface while the lysines point towards the surrounding media (9,10,16,41,42). Leu1, Leu4, Leu8, and Leu11 have α-carbons close to the surface and are probably interacting strongly with the PS surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter constraint, the distance of the α-carbon to the surface, can be estimated from the peptide sequence and the known orientation of the entire peptide on hydrophobic surfaces. It has been shown that the peptide assumes an α-helical secondary structure on polystyrene and that the leucine ensemble is generally oriented towards the interface while the lysines point towards the surrounding media (9,10,16,41,42). Leu1, Leu4, Leu8, and Leu11 have α-carbons close to the surface and are probably interacting strongly with the PS surface.…”
Section: Discussionmentioning
confidence: 99%
“…Sum frequency generation (SFG) spectroscopy has proven to be an increasingly powerful technique for probing protein films in situ at the solid-liquid interface (8)(9)(10)(11)(12)(13)(14)(15)(16). According to the "selection rules" of SFG, only molecular groups in proteins or peptides at an interface that have a net order will contribute to the measured signal (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it can be considered unlikely that these porphyrine-carrying molecules exhibit the orientation preference required for SFG activity. Other NH containing compounds such as amino acids, peptides or amino sugars [Mermut et al, 2006;Aluwihare and Meador, 2008] are expected to yield signal around 3300 cm −1 [Shultz et al, 2000]. Consequently, (1) the presence of additional OH group containing compounds and/or (2) confined water molecules or water clusters residing in dense organic monolayers may serve as more probable explanations.…”
Section: Surfactant Effectsmentioning
confidence: 99%
“…Kim et al, 2004;Dreesen et al, 2004b;Paszti et al, 2004;X. Chen et al, 2005a;Clarke et al, 2005;Mermut et al, 2006;Phillips et al, 2007;York et al, 2007;Weidner et al, 2009Weidner et al, , 2010Baugh et al, 2010;Boughton et al, 2010;Ye et al, 2010;Nguyen et al, 2010). We believe it is important to summarise these protein related SFG studies and make it accessible to researchers in the fields of biosensors, biomaterials and biomedical diagnostic devices.…”
Section: Introductionmentioning
confidence: 99%